The seven princesses - Coh, Smiljana (RP Kids, Running Press Kids, 2016)
Once upon a time, there were seven princess sisters who did everything together, from horseback riding to jumping in royal leaf piles to throwing legendary piñata parties. But one day, they had the biggest fight in the entire history of princess fighting. There was no worse sound than the sound of this fight. Will the sisters ever find a way to fill their kingdom with sounds of laughter and playing again? Princesses of all sizes will royally delight in this modern-day fairy tale of sibling rivalry, adventure, and unconditional sisterly love.